Applications of stainless steels - Dionicio Padilla, Eusebio (1999)
The main reason for the existence of stainless steel is its resistance to corrosion. Chromium is the main alloying element and stainless steel must contain at least 11%. Chromium is a reactive element, but chromium containing alloys are passivated, exhibiting excellent resistance to many environments. A large number of corrosion resistant alloys with defined mechanical properties are available, varying the cost considerably. In our environment, despite the fact that the demand for these materials has increased significantly, the national industry continues to cover almost 90% of its needs for stainless steels with just two or three types of these alloys, the most representative being AISI 304 and AISI 316.